Dynamics of estuarine muds a manual for practical applications - Whitehouse, Richard (Thomas Telford, 2000)
This work explores the ability to predict the movement of cohesive sedmient within coastal, estaurine or inland waters and describes the significant economical and ecological importance in the development of new engineering works and the maintenance of existing installations.